THE EFFECTIVITY OF CREDIT FOR BUSINESSES PROGRAM (KUR) DISTRIBUTION IN MALUKU AND MALUKU UTARA PROVINCES IN PERIOD OF 2010-2014 - Munandar, Yusuf . (FEB Universitas Sam Ratulangi Manado, 2017)
This research is conducted to know and explain the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Province and Maluku Utara Province. The research show that the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Province was decreasing that is the mistargeted ratio in 2014 as 1,57% was higher than the mistargeted ratio in 2010 as 0,00% and the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Utara Province was increasing that is the mistargeted ratio in 2014 as 1,85% was much lower than the mistargeted ratio in 2010 as 23,54%.Keywords : Credit for business, economic development, productive sector, poverty, working capital.